2017
DOI: 10.1177/1591019917708568
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular treatment of wide-neck intracranial bifurcation aneurysms with ‘Y’-configuration, double Neuroform® stents-assisted coiling technique: Experience in a single center

Abstract: Background Intracranial wide-neck aneurysms at the arterial bifurcations, especially in the aneurysms where the bifurcating branches emanate directly from the base of the aneurysm, have been particularly difficult on which to perform endovascular treatment. The ‘Y’-configuration, double stent-assisted coil embolization is an option for the treatment of these difficult aneurysms, allowing the closure of the aneurysm, preserving the parent arteries. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 24 publications
(54 reference statements)
0
11
0
Order By: Relevance
“…Although infrequently specified in the included studies, most Neuroform stents were the older generation devices. Castaño et al 26 described a series of patients treated with different generations of Neuroform stents, including the Neuroform Atlas Stent System in past years, reporting 95% occlusion and a very low rate of treatment-related complications (2.5%) after Y-stent placement. The authors reported that in their experience, open-cell stents had good conformability to tortuous anatomies, minor rectification of the vessels, high vessel wall apposition, and easier microcatheterization through the mesh of the first stent.…”
Section: Closed-cell and Open-cell Stentsmentioning
confidence: 99%
“…Although infrequently specified in the included studies, most Neuroform stents were the older generation devices. Castaño et al 26 described a series of patients treated with different generations of Neuroform stents, including the Neuroform Atlas Stent System in past years, reporting 95% occlusion and a very low rate of treatment-related complications (2.5%) after Y-stent placement. The authors reported that in their experience, open-cell stents had good conformability to tortuous anatomies, minor rectification of the vessels, high vessel wall apposition, and easier microcatheterization through the mesh of the first stent.…”
Section: Closed-cell and Open-cell Stentsmentioning
confidence: 99%
“…They represent challenges to clinical understanding and treatment because of their anatomical variations of the Acoma complex. The classifications of Acoma aneurysms in previous studies were based on surgical findings, such as the relationship between the aneurysm projection and the axis defined by the pericallosal artery, 7 the relationship between the aneurysm projection and A2 segment plane, 8 the relationship between the aneurysm projection and A1 segment morphology, 9 and the relationship between the aneurysm and the parent artery. 2,3 The previous classifications of Acoma aneurysms based on intraoperative observations are limited by the differences of their surgical approaches, intraoperative anatomical field, and lack of the standard position leading to the complex and divergent classifications.…”
Section: Discussionmentioning
confidence: 99%
“…They represent challenges to clinical understanding and treatment because of their anatomical variations of the Acoma complex. The classifications of Acoma aneurysms in previous studies were based on surgical findings, such as the relationship between the aneurysm projection and the axis defined by the pericallosal artery, 7 the relationship between the aneurysm projection and A2 segment plane, 8 the relationship between the aneurysm projection and A1 segment morphology, 9 and the relationship between the aneurysm and the parent artery. 2,3…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, there have been few reports on its application in the treatment of IC-PC aneurysms. 8,[15][16][17][18] According to a meta-analysis of 27 studies, including 750 aneurysms in 744 patients reported by Cagnazzo et al, the complete occlusion rate by Y-SAC was 95.4%, recanalization rate was 3%, the treatment-related complication rate was 8.9%, the morbidity rate was 2.4%, and the mortality rate was 1.1%. 6) These rate differed among the stents used for Y-SAC; the complete occlusion rate was 96% and the treatment-related complication rate was 6.5% with the Enterprise ( Codman & Shurtleff, Raynham, MA, USA), the complete occlusion rate was 92% and the complication rates was 11% with the LVIS or LVIS Jr (MicroVention, Tustin, CA, USA), and the complication rates were 94% and 14%, respectively, with the Neuroform (Stryker).…”
Section: Discussionmentioning
confidence: 99%
“…Reports about Y-SAC for IC-PC aneurysms are limited, and a total of 12 cases, including four treated by crossing Y-SAC [15][16][17][18] and eight treated by kissing Y-SAC, 8) were found in our review of the relevant literature. The detailed content of treatment was only described in two cases treated by crossing Y-SAC.…”
Section: Discussionmentioning
confidence: 99%